Coercivity Enhancement of Sintered Nd-Pr-Fe-B Magnets by Cost-Effective Grain Boundary Diffusion of Dy/Tb Films - Xin-De Zhu; Mei Wang; Yong-Jiang Yu; Qian Wang; Fei Wang; Peng-Fei Wang; Bin Jia; Cong Wang; Bin Zhou (Crystals, 2023)
High-performance sintered Nd-Pr-Fe-B magnets were successfully prepared by depositing Dy/Tb films on the surface using magnetron sputtering, which resulted in superior grain boundary diffusion (GBD) under heat treatments. The course of the diffusion was assessed using an electron probe microanalyzer (EPMA) and inductively coupled plasma (ICP). The magnetic properties and thermal stability of the magnets before and after diffusion were investigated. The results show that, mainly due to the increased and optimized Nd-Pr-rich phases and the formation of the (Nd,Pr,Dy/Tb)2Fe14B shell structure surrounding the (Nd,Pr)2Fe14B grains, the coercivity of the Dy- and Tb-diffused magnets was enhanced from 16.7 kOe to 24.8 kOe and 28.4 kOe, respectively, while the corresponding maximum energy product (BHmax) was 48.1 MGOe and 48.5 MGOe, respectively. The consumption of Dy/Tb in this work (0.35 wt% Dy in the Dy-diffused magnet and 0.42 wt% Tb in the Tb-diffused magnet) is much lower than that of previously reported magnets with comparable coercivity. Furthermore, Dy- or Tb-diffused magnets exhibit better thermal stability than that of the original magnet, owing to the better resistance to thermal disturbances of the magnets with optimized microstructure. This work can provide useful guidance for preparing Nd-Fe-B magnets with low cost and high performance.